Mobility Trajectories at the End of Life: comparing clinical condition and latent class approaches - Lunney, June R. (J Am Geriatr Soc, 2018)
OBJECTIVE: We assessed mobility disability trajectories before death in a large sample of very old adults using two analytic approaches to determine how well they correspond. DESIGN: Decedent sample from the Health, Aging and Body Composition Study (Health ABC). Data were collected between 1997 and 2015. SETTING: A population-based sample of 3075 participants, randomly selected from well-functioning White Medicare beneficiaries and all African American community residents meeting age criteria (70–79 years) in Pittsburgh, PA, and Memphis, TN. PARTICIPANTS: Of the 1991 participants who died by the end of the study, 1410 were interviewed for three years prior to death, including an interview six months before dying. EXPOSURES: Participants were interviewed in person or by phone at least every six months throughout the study. MEASUREMENTS: We analyzed self-reported mobility collected prospectively at six month intervals during the last three years of life. We derived trajectories in two ways: first by averaging decline within decedent groups pre-specified by clinical conditions and, second, by estimating trajectory models using maximum-likelihood semiparametric modeling. RESULTS: Classification by clinical conditions (sudden death, terminal, organ failure and frailty) accounted for 98% of decedents and produced groups with different characteristics. Five disability trajectories were identified: late decline, progressive disability, moderate disability, early decline, and persistent disability. Disability trajectory and clinical condition grouping both confirmed previous research but were only marginally related. CONCLUSIONS: Derived disability trajectories and grouping by clinical conditions both provide useful information about different facets of the end-of-life experience. The lack of fit between them suggests a need for greater attention to heterogeneity in disability in the period before death.